2017
DOI: 10.1620/tjem.242.53
|View full text |Cite
|
Sign up to set email alerts
|

Remission Induction Therapy with Rituximab for Microscopic Polyangiitis: A Feasibility Study

Abstract: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is systemic vascular inflammation. Microscopic polyangiitis (MPA) is a major type of AAV in Japan. MPA often affects the kidneys and lungs, leading to death if untreated. Induction therapy (i.e., initial treatment) for MPA has not been optimized, although methylprednisolone and cyclophosphamide are commonly used. Recently, rituximab (RTX) (a monoclonal antibody against the protein CD20) has also been used to treat refractory AAV. RTX at 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Moreover, another study investigated low-dose RTX therapy as an induction regimen and showed that low-dose RTX therapy was effective in refractory AAV patients, which has a beneficial effect because of the expensive price [ 87 ]. Satio et al [ 88 ] investigated a single dose of 375 mg/m 2 and confirmed that a single dose of RTX is effective in MPA and was associated with decreasing economical damage. However, Moog et al [ 89 ] showed that a single dose of RTX combined with other immunosuppressive therapies is not as effective as a licensed RTX therapy regimen.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, another study investigated low-dose RTX therapy as an induction regimen and showed that low-dose RTX therapy was effective in refractory AAV patients, which has a beneficial effect because of the expensive price [ 87 ]. Satio et al [ 88 ] investigated a single dose of 375 mg/m 2 and confirmed that a single dose of RTX is effective in MPA and was associated with decreasing economical damage. However, Moog et al [ 89 ] showed that a single dose of RTX combined with other immunosuppressive therapies is not as effective as a licensed RTX therapy regimen.…”
Section: Resultsmentioning
confidence: 97%
“…For the induction of remission of AAV, it is common to administer RTX at a dose of 375 mg/m 2 every week for 4 consecutive weeks or 1,000 mg twice every 2 weeks ( 6 ). Regarding the number of administrations and dosage of RTX, single infusion of RTX was effective not only at a dose of 375 mg/m 2 but also at a dose of 500 mg/body for remission induction of AAV ( 4 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of RTX at 500 mg, the dosage that was decided in order to reduce the risk of infections, was investigated and compared with that of azathioprine as maintenance treatment of AAV patients; RTX showed a better outcome than azathioprine ( 8 ). The risk of infection with RTX may be lower with a single infusion of RTX than at the normal dose ( 7 , 9 ). In our case, B-cell depletion was achieved with a single dose of RTX at 500 mg and was maintained for six months.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab has shown positive results for people with certain types of vasculitides, including microscopic polyangiitis and Wegener's granulomatosis . Rituximab is a synthetic antibody that selectively reduces the number of B cells circulating in the blood, and it helps to decrease inflammation without the use of steroids.…”
Section: Concluding Remarks and Therapeutic Perspectivementioning
confidence: 99%
“…Wegener's granulomatosis. 81,82 Rituximab is a synthetic antibody that selectively reduces the number of B cells circulating in the blood, and it helps to decrease inflammation without the use of steroids. A humanized anti-human IL-6 receptor antibody tocilizumab has been successfully used and in eight cases of refractory large-vessel vasculitis and CGA.…”
Section: Con Clud Ing Remark S and Ther Apeuti C Per S Pec Tivementioning
confidence: 99%